Influencing Factor of Waste Generation towards Environmental Sustainability and Economic Viability - Chan, Darren, Chee Shern; Chua, Siew Woon; Pok, Wei Lun; Soon, Shi Wen; Tio, Fang Kee; Su, Wenqian (INTI International University, 2024)
In today's rapidly evolving industrial landscape, the efficient management of industrial waste has become an imperative for both environmental sustainability and economic viability. This report explores the key factors that influence industrial waste generation and how the application of information technology and MIS is important in the minimizing waste management challenges. Industrial wates refer to those material which discarded or couldn’t be used in manufacturing like excess raw material, broken or defective product. The manufacturing process could generate a huge amount of waste materials, ranging from dangerous chemicals to non-recyclable by products. This research utilizing both quantitative approaches, collect primary data through questionnaire and data collection instruments will be using Google form and qualitative approach, using secondary data from existing sources as supporting resources. This report has examined the key factors influencing industrial waste generation and emphasized the vital role of information technology and information systems in addressing waste management challenges. In addition, the foundation of equipment efficiency lies in regular maintenance protocols. Hence, implementing rigorous and proactive maintenance practices is essential to ensure that equipment remains in top condition.